Carbon Dots ZIF-8 Membrane for Lead(II) Removal - Muhammad Shamil, Soffian (UNIMAS, 2025)
Heavy metal pollution has become a significant problem in past years, owing to the fast growth of polluting industries. The most hazardous heavy metals, such as lead(II), might have catastrophic consequences for human health and this problem should be overcome. Therefore, a reasonable approach to tackle this issue is by introducing a membrane material derived from the combination of ZIF-8 and carbon dots material to remove the lead(II) from the aqueous solution. The aim of this research study is to fabricate carbon dots-ZIF-8 (CDs@ZIF-8) membrane and to evaluate the performance of modified ZIF- 8 membrane on the removal of heavy metal. This study was conducted through three phases in brief. The study started with the preparation of CDs@ZIF-8 membrane which involved the preparation from sago hampas, modification of alumina hollow fibre membrane using APTES and insitu solvothermal preparation. The second phase involved various kinds of characterization analysis; FTIR, SEM, EDX, XRD and PSA. Subsequently, the removal of lead(II) by CDs@ZIF-8 membrane performance had been evaluated through the batch adsorption study and cross-flow filtration system. The 160°C CDs@ZIF-8 membrane exhibits better adsorption performance than the 200°C CDs@ZIF-8 membrane with a maximum lead(II) absorption potential of 95.16 mg/g and remove up to 74.73% of the lead(II) ions with the flux of 38.55 Lm-2h-1. The Freundlich isotherm and pseudo-second-order model best matched the lead(II) adsorption process onto the CDs@ZIF-8 membrane.